Energy storage in symmetric and asymmetric supercapacitors based in carbon cloth/polyaniline-carbon black nanocomposites - Bavio, Marcela Alejandra (2015)
In this work, the construction of electrochemical capacitors using polyaniline-carbon black nanocomposites as electrode material is described. Symmetric and asymmetric cells were assembled. The active material was supported on carbon cloth acting as current collector as well. The electrolyte was H2SO4 0.5 M, and the selected potential range was 1V. The electrochemical behavior of the arrayed supercapacitors was studied by cyclic voltammetry and galvanostatic charge/discharge runs. At a constant current density of 0.3 A/g, a specific capacitance value of 1039 F/g was obtained for a symmetric assembly using both electrodes prepared with polyaniline and carbon black nanocomposites. When the set is asymmetric, being the positive electrode made of polyaniline and carbon black nanocomposites, the specific capacitance value is 1534 F/g. For the latter array, the specific power and energy density values are 300 W/kg and 426 Wh/kg at 0.3 A/g, and 13 700 W/kg and 28 Wh/kg at 13.7 A/g. These results suggest a good capacity of fast energy transfer. Moreover, this asymmetric supercapacitor demonstrated a high stability over 1000 cycles being the loss of only 5%.